Cytotoxic and proinflammatory responses induced by ZnO nanoparticles in in vitro intestinal barrier. Issue 8 (24th April 2019) - Colombo, Graziano; Cortinovis, Cristina; Moschini, Elisa; Bellitto, Nicholas; Perego, Maria Chiara; Albonico, Marco; Astori, Emanuela; Dalle‐Donne, Isabella; Bertero, Alessia; Gedanken, Aharon; Perelsthein, Ilana; Mantecca, Paride; et al.
Abstract: ZnO nanoparticles (NPs) are widely used nowadays, thus the gastrointestinal exposure to ZnO NPs is likely to be relevant and the effects on the intestinal barrier should be investigated. Polarized Caco‐2 cells were exposed from the apical (Ap) and basolateral (Bl) compartments to increasing concentrations (0, 10, 50 and 100 μg/mL) of sonochemical (sono) and commercial ZnO NPs. The transepithelial electrical resistance (TEER), cell viability, proinflammatory cytokine release and presence of protein oxidative damage were evaluated after exposure. TEER was not significantly affected by Ap exposure to either sono or commercial ZnO NPs at any tested concentrations. After Bl exposure to sono ZnO NPs (all the concentrations) and to 100 μg/mL of commercial ZnO NPs TEER was decreased ( P  < 0.05). Ap and Bl exposure to 100 μg/mL sono ZnO NPs and Ap exposure to 50 μg/mL commercial ZnO NPs induced a significant ( P  < 0.05) release of interleukin‐6. A significant ( P  < 0.05) release of interleukin‐8 was observed after Ap exposure to ZnO NPs at 100 μg/mL and after Bl exposure to sono ZnO NPs at 100 μg/mL. Ap or Bl exposure to sono or commercial ZnO NPs did not affect tumour necrosis factor‐alpha secretion or protein sulphydryl oxidation. In conclusion, the ZnO NP exposure from the Ap compartment appeared almost safe, while the exposure through the basal compartment appeared to be more hazardous and the different NP size and crystallinity seem to affect the mode of action, but further studies are necessary to elucidate better these toxicity mechanisms. Abstract : In this study, polarized Caco‐2 cells were exposed (apical/basolateral sides) to 0, 10, 50 and 100 μg/mL of sonochemical and commercial zinc nanoparticles (ZnO NPs). Then transepithelial electrical resistance, cell viability, proinflammatory cytokine release and presence of protein oxidative damages were evaluated. Transepithelial electrical resistance was decreased ( P  < 0.05) after basolateral exposure to ZnO NPs. Exposure to ZnO NPs also induced a significant ( P  < 0.05) release of interleukin‐6 and ‐8, whereas tumour necrosis factor‐alpha secretion or protein sulphydryl oxidation seemed not affected.